(3COjHs - (3MSjf, Wgs ((3GdbGgQIs (3GdgjFI GdeUQjI GdYGeI dbUhQ GdKbGaIs, 2024)
(3EfgeG SjQJGf eJcGedJGf(B: (3SjQI PGJjI NGUI HGdcGJH, hSjQI ZjQjI eJYdbI HGdCOjH, haj faS GdhbJ gj QhGjI afjI JYJeO Ydi GdJNjjd hGdGdJaGJ hGdJThjb hGdGSJWQGO hGdGgJeGe HUfGYI GdHjGf hHdGZI GdJUhjQ; hgPG eeG jLYd (S0(3Wg MSjf(S1 (3CMO QhGO GdCOH GdYQHj GdMOjK GdCaPGP(B. (3ceG Cf aj gPg GdSjQI EOGfI dLjd ef GdeKbajf GdYQH GdPjf bUOhG ChQhHG HMkKG Yf GdYde hGSJceGkdG dOQGSGJge GdYdjG, aGfHgQhG HMVGQI GdZQH, hdcfge HOkdG ef Cf jSJajOhG ef GdYdhe hGdeYGQa hGdBOGH, SbWhG aj GdZhGjI hGdQPjdI haJfI GdNWjFI, h GfZeShG aj HhJbI GdTQ hGdaSGO, hGdGfSjGb GdCYei ddZQH hGdEjeGf HadSaJg GdeGOjI GdeMVI hCacGQg GdefMdI(B. (3EfgG eCSGI (S0(3COjH(S1 (3Cafi YeQg aj GdCOHs
Keywords: (3Wg MSjfs -- (3JQGLes; (3GdCOHGA GdYQHs -- (3eUQs; (3GdJQGLe GdCOHjIs